The fastest unbound star in our Galaxy ejected by a thermonuclear supernova - Geier, Stephan; Furst, Felix; Ziegerer, Eva; Kupfer, Thomas; Heber, Ulrich; Irrgang, Andreas; Wang, Bo; Liu, Z.; Han, Z.; Sesar, B.; Levitan, D.; Kotak, R.; et al. (Science, 2015)
Hypervelocity stars (HVSs) travel with velocities so high that they exceed the escape velocity of the Galaxy. Several acceleration mechanisms have been discussed. Only one HVS (US 708, HVS 2) is a compact helium star. Here we present a spectroscopic and kinematic analysis of US 708. Traveling with a velocity of similar to 1200 kilometers per second, it is the fastest unbound star in our Galaxy. In reconstructing its trajectory, the Galactic center becomes very unlikely as an origin, which is hardly consistent with the most favored ejection mechanism for the other HVSs. Furthermore, we detected that US 708 is a fast rotator. According to our binary evolution model, it was spun-up by tidal interaction in a close binary and is likely to be the ejected donor remnant of a thermonuclear supernova.